Mild and asymptomatic influenza B virus infection among unvaccinated pregnant persons: Implication for effectiveness of non-pharmaceutical intervention and vaccination to prevent influenza. Issue 3 (16th January 2023) - Chen, Liling; Levine, Min Z.; Zhou, Suizan; Bai, Tian; Pang, Yuanyuan; Bao, Lin; Tan, Yayun; Cui, Pengwei; Zhang, Ran; Millman, Alexander J.; Greene, Carolyn M.; Zhang, Zhongwei; et al.
Abstract: Background: We estimated symptomatic and asymptomatic influenza infection frequency in community-dwelling unvaccinated pregnant persons to inform risk communication. Methods: We collected residue sera from multiple antenatal-care blood draws during October 2016–April 2017. We determined influenza infection as seroconversion with ≥ 4-fold rise in antibody titers between any two serum samples by improved hemagglutinin-inhibition assay including ether-treated B antigens. The serology data were linked to the results of nuclei acid testing (rRT-PCR) based on acute respiratory illness (ARI) surveillance. Results: Among all participants, 43 %(602/1384) demonstrated serology and/or rRT-PCR evidenced infection, and 44 %(265/602) of all infections were asymptomatic. ARI-associated rRT-PCR testing identified only 10 %(61/602) of total infections. Only 1 %(5/420) of the B Victoria cases reported ARI and had a rRT-PCR positive result, compared with 33 %(54/165) of the H3N2 cases. Among influenza ARI cases with multiple serum samples, 19 %(11/58) had seroconversion to a different subtype prior to the illness. Conclusions: The incidence of influenza B infection in unvaccinated pregnant persons is under-estimated substantially. Non-pharmaceutical intervention may have suboptimal effectiveness in preventing influenza B transmission due to the less clinical manifestation compared to influenza A. The findings support maternal influenza vaccination to protect pregnant persons and reduce consequent household transmission.